EFFECT OF ZINC OXIDE NANOPARTICLES AGAINST PHYTOPHTHORA SPP. CAUSING DURIAN DISEASES IN VITRO - Keeratirawee, Kanchalar; Kongtragoul, Pornprapa; Pantakan, Sansanee (My University, 2024)
The efficiency of zinc oxide nanoparticles (ZnO-NPs) in inhibiting Phytophthora spp. growth in both durian fruits and stems is demonstrated. The size of ZnO-NPs used was in range of 25-50 nm in diameter. Diseased durian sample were collected from a durian orchard located in southern of Thailand. The pathogen of diseased durian was isolated for subsequent morphological identification. Three distinct strains of Phytophthora spp. (designated as PHY41, PHY45, PHY49) were successfully isolated and were found in colonies with rings and stellate pattern, ovoid, limoniform sporangium with semi-papillate or papillate, and formation chlamydospores. All isolates were exhibiting 100% pathogenicity on durian, as indicated by the disease incidence (DI). The concentration of ZnO-NPs played a crucial role in suppressing the growth of Phytophthora spp. in all isolates. Higher concentration of ZnO-NPs resulted in increased inhibition of growth. ZnO-NPs at the concentration of 2000 µg/mL effectively suppressed the mycelial growth of all fungi isolates at 57.76-69.84%. Additionally, ZnO-NPs at the concentration of 500 µg/mL completely inhibited the sporulation only in the PHY49 strains. Furthermore, ZnO-NPs concentration ranging from 1000-2000 µg/mL resulted in completed inhibition in sporulation in all Phytophthora spp. isolates. The result demonstrated that ZnO-NPs at all concentrations effectively delayed the germination of Phytophthora spp.
Keywords: Durian diseases; Inhibit; Pathogenicity test; Phytophthora spp; ZnO-NPs